Epistimology and Curriculum of Islamic Education from the Perspective of Majid 'Irsan Al-Kilani: Epistimologi dan Kurikulum Pendidikan Islam Perspektif Majid ‘Irsan Al-Kilani - Mu'ammar, Muhammad Arfan; Muchtar, Nicky Estu Putu (Universitas Muhammadiyah Sidoarjo, 2024)
The research aims to observe the perspective of Majid ‘Irsan Al-Kilani about epistemology and curriculum in Islamic education. The research used descriptive qualitative with the type of library research because of the research object and data collection. The source of data in the research was Majid ‘Irsan Al-Kilani’s books entitled Majid ‘Irsan Al-Kilani dengan judul Manāhij-ut tarbiyyat-il islāmiyyah wal murabbūna al’āmilūna fīhā, dan Falsfat-ut tarbiyyat-il islāmiyyah. Content analysis was conducted as an analysis technic in this research. Finally, this research found that epistemology in Islamic education according to Majid ‘Irsan Al-Kilani was the essence of Islamic education was an effort to lead students to reach the level “aḥsan-u taqwīm” with the tools used being revelation, mind, and the senses. Al-Kilani also concluded that the scope of Islamic education includes four aspects, namely aspects of intellectual preparation and priority of Islamic knowledge (tazkiyat i’dād-il fikriy wa taqdīm-il ma’ārif-il islāmiyyah), skill preparation aspect. Then, the concept of curriculum in Islamic education according to Al-Kilani, there were three points, as Tilawah al-Ayat, 2. Al-Tazkiyah, 3. Ta’lim al-Kitab wa al-Hikmah Keywords: Epistemology, Curriculum, Islamic Education, Majid ‘Irsan Al-Kilani